Explaining the cash-in-hand consumer culture in the European home repairs and renovations sector. Issue 3 (8th July 2020) - Williams, Colin; Kosta, Brunilda
Abstract : Purpose: The purpose of this paper is to explain who purchases undeclared home repairs and renovations and their motives to tackle the cash-in-hand consumer culture. The conventional view has been that undeclared home repairs and renovations are sought by those consumers needing to save money and desiring a lower price. Here, this is evaluated critically. Design/methodology/approach: To do so, evidence from a 2019 Eurobarometer survey involving 27, 565 face-to-face interviews in 28 European countries is reported. Findings: The finding is the need for a nuanced and variegated understanding of who purchases undeclared home repairs and renovations and why. Lower price is their sole rationale in just 25% of purchases, one of several rationales in 34% of cases and not a reason in the remaining 42% of purchases. Besides a lower price, consumers purchase undeclared not only unintentionally but also to circumvent the failings of formal sector provision in terms of its availability, speed and quality, as well as for social and redistributive rationales. Practical implications: To reduce the cash-in-hand consumer culture, not only are incentives needed to persuade consumers to purchase declared along with awareness-raising campaigns about the benefits of purchasing declared services but initiatives are also needed to improve the availability, speed, reliability and quality of formal provision and to address undeclared purchases conducted for social and redistributive purposes. Originality/value: This paper improves understanding of how governments can stop consumers asking "how much for cash" and reduce demand for undeclared home repair and renovation services.